Bezlotoxumab (BEZ) for Prevention of Clostridium Difficile Infection (CDI) Recurrence (rCDI): Outcomes in Patients with Substantial Renal Impairment (SRI). (4th October 2017) - Golan, Yoav; DuPont, Herbert L; Aldomiro, Fernando; Jensen, Erin H; Hanson, Mary E; Dorr, Mary Beth
Abstract: Background: CDI in patients with SRI is harder to treat and is associated with higher recurrence. MODIFY I/II found that BEZ, a monoclonal antibody against C. difficile toxin B, is superior to placebo (PBO) at preventing rCDI in patients receiving standard of care antibiotics (SoC). This post hoc analysis assessed efficacy of BEZ in patients with SRI in the MODIFY studies. Methods: MODIFY I/II mITT populations were pooled to estimate initial clinical cure (ICC), rCDI, and mortality through 12 weeks. Estimated glomerular filtration rate (eGFR) was calculated with the Modified Diet in Renal Disease (MDRD) method. SRI was defined as eGFR <60 mL/minute/1.73 m 2 . ICC was defined as SOC ≤16 days and no diarrhea on the 2 days after SoC end. rCDI was defined as diarrhea and toxigenic C. difficile in stool. Mortality within 90 days after randomization was summarized. Results: Of the included 1554 patients, 1101 had no SRI (≥90: n = 612; 60 to < 90: n = 489); 430 had SRI (30 to <60: n = 290; 15 to <30: n = 71; <15: n = 69); 23 had unknown eGFR. 87% of SRI patients had ≥1 risk factor for rCDI. Relative to patients without SRI, more patients with SRI were ≥65 years (69% vs. 44%), immunocompromised (25 vs. 20%), had ribotype 027 (25% vs. 17%), and used concomitant antibiotics during SoC (41% vs. 31%) or after SoC (36% vs. 28%). SRI patients had more severe CDI (21% vs. 14%), lower CDI cure (78.4% vs. 80.1%), higher rCDI (31.6% vs. 27.8%), and death (11.6% vs. 5.3%) In the SRI cohort, more BEZ vs. PBO patients were inpatients (81% vs. 72%), ≥65 years (72% vs. 65%), immunocompromised (28 vs. 22%), and used systemic antibiotics after SoC ended (40% vs. 32%). The rate of ICC was similar between treatment groups and the rCDI rate was significantly less the BEZ vs. PBO group (Table). Conclusion: SRI was associated with worse CDI outcomes. BEZ given with SoC significantly reduced rCDI in patients with SRI and could benefit this hard to treat population. Disclosures: Y. Golan, Merck & Co., Inc.: Grant Investigator, Scientific Advisor and Speaker's Bureau, Research support and Speaker honorarium; Pfizer: Scientific Advisor, Speaker honorarium; Allergab: Grant Investigator and Scientific Advisor, Research grant and Speaker honorarium; The Medicines Company: Scientific Advisor, Speaker honorarium; Seres Pharmaceuticals: Scientific Advisor, Speaker honorarium; H. L. DuPont, BioK International, Salix: Consultant, Consulting fee; University Rebiotix, Seres, Takeda: Grant Investigator, Grant recipient; F. Aldomiro, BMS & ViiV: Scientific Advisor, Consulting fee; MSD, Viiv, Astellas & Pfizer: Participated in Clinical Trials, Research support; E. H. Jensen, Merck & Co., Inc.: Employee, may own stock/hold stock options in Company; M. E. Hanson, Merck & Co. Inc.: Employee, may own stock/hold stock options in the Company; M. B. Dorr, Merck & Co., Inc.: Employee and Shareholder, may own stock/hold stock options in the Company